2019
DOI: 10.1007/s11042-019-7663-8
|View full text |Cite
|
Sign up to set email alerts
|

Initialization-similarity clustering algorithm

Abstract: Classic k-means clustering algorithm randomly selects centroids for initialization to possibly output unstable clustering results. Moreover, random initialization makes the clustering result hard to reproduce. Spectral clustering algorithm is a two-step strategy, which first generates a similarity matrix and then conducts eigenvalue decomposition on the Laplacian matrix of the similarity matrix to obtain the spectral representation. However, the goal of the first step in the spectral clustering algorithm does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The Dual-index tags were used to classify the raw sequencing data by sample. Sequences read from the same locus were grouped using similarity clustering [51]. In general, only high-depth fragments were selected in each cluster group; low-depth segments were removed.…”
Section: Development Of Slaf Tags and Snp Markersmentioning
confidence: 99%
“…The Dual-index tags were used to classify the raw sequencing data by sample. Sequences read from the same locus were grouped using similarity clustering [51]. In general, only high-depth fragments were selected in each cluster group; low-depth segments were removed.…”
Section: Development Of Slaf Tags and Snp Markersmentioning
confidence: 99%
“…The execution time of the deterministic and incremental approaches has increased exponentially on multidimensional data 43 . The authors of References 19 and 44 demonstrated that nonrandomization and stable convergence produce excellent initial centroids. Nonrandomization and stable convergence are used to improve clustering performance and cluster initialization issues such as local optima, iterations, convergence speed, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering is the most exploratory task in big data mining and is used in numerous domains such as character and pattern recognition, 7 image segmentation and processing, 8,9 text analysis, 10 video processing, 11 social network analysis, 12 bioinformatics, 13,14 recommendation task, 15 wireless sensor, 16 document clustering, 17,18 molecular biology, 7 pattern recognition, 7 psychology, 19 medicine, 19 gene expression grouping, 20 business analysis, 21 software evolution, 21 educational data analysis, 21 data reduction and compression, 7,21 climatology, 21 sequence analysis, 21 field robotics, 21 and so forth. The unstructured data types are converted into feature vectors according to clustering algorithm for big data clustering.…”
mentioning
confidence: 99%
“…Clustering is used for segmenting or grouping data into clusters based on similarities and dissimilarities. Clustering is a multivariate statistical technique that achieves maximized within-cluster similarity and between-cluster dissimilarity based on similarity, dissimilarity and distance measures according to the nature of the data (Liu et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%